Nutritional Status of the Underfive Children at The Pediatric Ward of Dr. Pirngadi Hospital, Medan - Kaswadharma K. C.; Arizal Arizal; Endang D. Hamid; Iskandar Z. Lubis; Sjarika T. Tarigan (Indonesian Pediatric Society, 1992)
An observational study on the assesment of nutritional status of the underfive children at the pediatric ward of Dr. Pirngadi hospital, Medan was conducted during February to March 1990. Nutritional status was determined usi11.g the parameters of Weight/Age (WIA), Weight/Height (WIH) and Mid upper Arm Circumference (MUAC) in accordance with the Seminar on Nutritional Anthropometry 1975. One-hundred and eighty patients were included in this study, consisting of 115 (67, 6%) children less than one year and 65 (32, 4%) children 1 - 5 years. According to the Weight/Age parameter there were 46.7% wellnourished children 42.8% with moderate and 10.5% with severe malnutrition on admission, while on discharge they were 48.3%, 42.8% and 8.9% (p > 0.05) respectively. Weight/Height and Mid upper Arm Circumference parameters also failed to reveal significant differences. The duration of hospitalization ranged from 1 to 3 0 days (mean 5 days). The most predominant disease was gastroenteritis with dehydration (68.9%). In 54.4% of patients, breast-feeding had been given until 6 month of age, while supplementary food starting before the age of 2 months was found in 52.2% . The incidence of undernutrition in underfive children was high.